Heritage in Danger: Digital Conservation and a Reserve for the Future of the Benzú Rock Shelter and Cave (Ceuta, Spain) - Alejandro Muñoz-Muñoz; José Ramos-Muñoz; Eduardo Vijande-Vila; Juan Jesús Cantillo-Duarte; José Luis Ramírez-Amador; Salvador Domínguez-Bella; Serafín Becerra-Martín; Eduardo Molina-Piernas; Diego Fernández-Sánchez (Applied Sciences)
The archaeological complex of the Benzú rock shelter and cave, located in Ceuta (Spain), represents a heritage site of significant scientific and historical value that is currently at risk due to natural processes and, in particular, the activity of a nearby quarry. This site has been occupied from the Palaeolithic to the Bronze Age and consequently has been the subject of systematic research since 2002, focusing on its stratigraphic sequence, lithic technology, exploitation of marine resources, and the connection between both shores of the Strait of Gibraltar. With the aim of preserving this endangered heritage, a methodology based on advanced digital technologies such as photogrammetry, 3D laser scanning, and GNSS georeferencing has been implemented. These tools have enabled the creation of high-precision, three-dimensional models of the rock shelter and the cave, which are useful for both documentation and monitoring of their structural condition. In addition, fracture networks have been identified, revealing a high degree of geotechnical vulnerability, exacerbated by blasting activities at the nearby quarry. The project has produced a digital twin of the site in an open access format, serving not only for preventive conservation but also for its enhancement through virtual tours, augmented reality, and accessible outreach activities. This digitalization has been essential to facilitate the access to heritage, particularly in areas that are physically difficult to access. Finally, the integration of these digital resources into institutional policies for the sustainable management of heritage is proposed, highlighting the importance of interdisciplinary approaches that combine archaeology, geotechnology, and scientific communication. The experience at Benzú is presented as a replicable model for the protection, interpretation, and dissemination of heritage sites located in fragile and threatened environments.